DISTRIBUSI RAYLEIGH UNTUK KLAIM AGREGASI - Pramesti, Getut (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2011)
An Aggregation of claims are claims the sum of individual claims can be described in a distribution of collective risks that occur in a single period of insurance. Distribution is depicted in a probability density function and cumulative density function. These functions can also describe the characteristics of the distribution through the mean and variance. Writing this paper is to determine the aggregate claims model with a amount individual claims Rayleigh distributed and the number of claims Poisson distributed. Discussion of the results obtained showed that the model's claim depends on the aggregation of individual claims and the number of claims that occurred during the period of insurance. Keywords: Aggregation, Claim, Rayleigh